1993
DOI: 10.1021/bi00213a032
|View full text |Cite
|
Sign up to set email alerts
|

Membrane-bound conformation of a signal peptide: A transferred nuclear Overhauser effect analysis

Abstract: We have determined the conformation of an analogue of the Escherichia coli LamB signal peptide inserted into a model membrane using the transferred nuclear Overhauser effect (trNOE) NMR technique. In order to make NMR analysis feasible, a water-soluble LamB signal peptide analogue was designed by inserting three basic residues (KRR) into the N-terminal region of the wild-type sequence (with a Val-->Trp mutation for fluorescence measurements), viz., MMITLRKRRKLPLAVAVAAGWMSAQAMA-NH2. For the purpose of the trNOE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
68
0

Year Published

1995
1995
2008
2008

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 76 publications
(71 citation statements)
references
References 43 publications
3
68
0
Order By: Relevance
“…Signal Peptide Synthesis and Purification-The KRR-LamB signal peptide ( ϩ H 3 N-MMITLRKRRKLPLAVAVAAGVMSAQAMA-COO Ϫ ) and the ⌬78 variant ( ϩ H 3 N-MMITLRKRRKLPVAAGVMSAQAMA-C-OO Ϫ ) were synthesized and purified as described (13). The concentration of signal peptide in a concentrated stock solution in water was determined using quantitative amino acid analysis (conducted at the W. M. Keck Biopolymer Facility at Yale University).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Signal Peptide Synthesis and Purification-The KRR-LamB signal peptide ( ϩ H 3 N-MMITLRKRRKLPLAVAVAAGVMSAQAMA-COO Ϫ ) and the ⌬78 variant ( ϩ H 3 N-MMITLRKRRKLPVAAGVMSAQAMA-C-OO Ϫ ) were synthesized and purified as described (13). The concentration of signal peptide in a concentrated stock solution in water was determined using quantitative amino acid analysis (conducted at the W. M. Keck Biopolymer Facility at Yale University).…”
Section: Methodsmentioning
confidence: 99%
“…There is substantial evidence that SecA interacts with both the N-terminal signal sequence (6,(12)(13)(14)(15)(16)(17)(18)(19)(20)(21) that targets preproteins for export from the cytoplasm as well as the mature region of the preprotein (22,23). These binding interactions presumably allow SecA to transfer polypeptide segments to SecYEG.…”
mentioning
confidence: 99%
“…We exploited the ability of signal peptides to spontaneously insert into model bilayers in lipid vesicles to determine their membrane-associated conformation, using transferred nuclear Overhauser effect (trNOE) NMR. 25 We also studied the manner in which they associated with the membrane using paramagnetic broadening of the NMR signals arising from the bound conformations, 25 EPR of spin-labeled lipids in the presence of signal peptides, 26 and extensive mapping of fluorescently labeled signal peptides using a variety of exogenous aqueous or lipid-resident quenchers. 20,27,28 The picture that emerged was consistent with all these data: The charged N-terminal region of the signal peptide associates with the lipid head groups of the cis leaflet of the bilayer in an extended conformation, while the hydrophobic core inserts well into the acyl chain region in a helical conformation.…”
Section: Signal Peptide Conformations and Membrane Interactionsmentioning
confidence: 99%
“…It has been shown that membrane-spanning regions of several integral membrane proteins are helical (Deisenhofer et al, 1985;Yeates et al, 1987). The peptides gramicidin A (Killian, 1992) and Lam B (Wang et al, 1993) undergo a conformational change to an e-helix upon insertion into membranes.…”
Section: Conformational Switching: the Actions Of Denaturants And Alcmentioning
confidence: 99%